Nanotechnology applications in drug delivery and clinical diagnostics - Sdiri, Yosra (2024)
The following work focuses on the potential of nanoparticle-based strategies to transform healthcare, namely in drug delivery and clinical diagnosis. Additionally, it investigates the design and use of nanomaterials in such applications. A variety of nanocarriers, such as inorganic nanoparticles like silica, iron oxide, and gold, and polymeric nanoparticles including polymersomes, dendrimers, and nanogels, which contribute to the enhancement of to the drug delivery techniques, are described. The potential of lipid-based nanomaterials, such as liposomes, niosomes, and solid lipid nanoparticles, to improve drug bioavailability and targeting effectiveness is also discussed. Nano-based biomedical technologies, such as monitoring systems and nanobiosensors, demonstrate improvements in precision diagnostics and real-time patient monitoring in the diagnostic field. Focus is placed on the use of nanoparticles in cancer treatment, emphasizing their efficacy in targeted therapy and in theragnostic applications, which combine therapeutic and diagnostic properties. The monography also emphasizes on the optimization techniques for the safety and effectiveness of nanoparticles, namely increased drug loading capacity, targeted delivery, and biocompatibility. Lastly, the challenges and potential prospects of nanotechnology in healthcare are examined, considering both the revolutionary possibilities and the obstacles that must be removed for wider clinical application.